1970
DOI: 10.3329/jbau.v8i1.6401
|View full text |Cite
|
Sign up to set email alerts
|

Performance and genetic parameters of economically important traits of Black Bengal goat

Abstract: A nucleus-breeding flock of selected Black Bengal goat was established in the Bangladesh Livestock Research Institute (BLRI) with the objective of conservation and improvement of the breed. A total of 120 does of different generations (70=foundation stock, 45=First generation and 5=Second generation) and 20 bucks (15=Foundation stock and 5=First generation) were used to study the genetic parameters of Black Bengal goat on productive and reproductive traits. Animals were bred naturally. Goats were reared under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
32
7
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 14 publications
16
32
7
2
Order By: Relevance
“…For gestation length flock effect and generation effect was not significant. Similar results was reported by Faruque et al (2010) for generation one143.00 days and generation two 141.25 days. The effect of parity on gestation length was found to be non-significant in the present study.…”
Section: Litter Size and Litter Weightsupporting
confidence: 79%
See 1 more Smart Citation
“…For gestation length flock effect and generation effect was not significant. Similar results was reported by Faruque et al (2010) for generation one143.00 days and generation two 141.25 days. The effect of parity on gestation length was found to be non-significant in the present study.…”
Section: Litter Size and Litter Weightsupporting
confidence: 79%
“…Trends of increasing the litter size and litter weight are observed with the advancement of generation and parities (Table 2). Similar results was reported by Faruque et al (2010) for litter size at birth of (1.33 to 1.77) and litter weight at birth (1.27 to 2.21kg) increased significantly (P<0.01) as parity progressed. Hussain et al (2004) noticed that among the four parities, kid's birth weight was lowest in 1st parity does compared to 2nd, 3rd and 4th parity.…”
Section: Litter Size and Litter Weightsupporting
confidence: 77%
“…Husain et al (1996) reported that weight at birth varied significantly (p<0.01) according to sex in Black Bengal goats, the male kids have higher birth weight (1.06±0.02 kg) than females (0.93±0.02 kg) which are similar to this study. Faruque et al (2010) reported that birth weight of kids of Black Bengal goat were 1.49±0.13 and 1.28±0.11 kg, respectively for intensive and semi intensive rearing system. Paul (2012) reported that average birth weight (kg) of kids of Black Bengal goat in Nucleus Breeding Flock (NBF) at Bangladesh Agricultural University, Modhupur, and Nilphamari were 1.09±0.27, 1.09±0.25 and 1.10±0.27 kg, respectively.…”
Section: Birth Weightmentioning
confidence: 99%
“…In spite of promises of Black Bengal goat amongst the world goat genetic resource the systematic information on production parameters in Black Bengal goat is very limited, although a lot of work has been done on various parameters of Black Bengal goat including productive and reproductive traits (Amin et al 2001;Faruque et al 2010). It is essential to compile the parameters by which Black Bengal goat can be described distinctively from others, which will be helpful for the breeders as well as farmers for the selection of goat.…”
Section: However There Have Sizable Genetic Variations In Different Ementioning
confidence: 99%